Apple and Blueberry Synergies for Designing Bioactive Ingredients for the Management of Early Stages of Type 2 Diabetes. Issue 4 (1st May 2016) - Agustinah, Widya; Sarkar, Dipayan; Woods, Floyd; Shetty, Kalidas
Abstract: Type 2 diabetes is an epidemic in both developed and developing countries. The aim of this research was to evaluate the synergistic health benefits of apple cider and blueberry juice combinations for relevance in the potential management of early stages type 2 diabetes using in vitro assays. Inhibitory activity of α‐amylase, α‐glucosidase and angiotensin‐1‐converting enzyme (ACE) in the juice combinations were analyzed and correlated with the total soluble phenolic content and antioxidant activity. While the total soluble phenolic content increased with the increasing blueberry juice proportion in the juice combinations, the ACE inhibitory activity decreased. The antioxidant activity was maintained at its maximum level (50–70%) in all combinations. High α‐glucosidase inhibitory activity was positively correlated with the total soluble phenolic content. A combination of 80% apple cider and 20% whole blueberry juice had optimum anti‐hyperglycemia and anti‐hypertension properties based on in vitro assays. Practical Applications: Apple cider and blueberry juice combination was investigated as a strategy to explore the potential health benefits for the management of hyperglycemia and hypertension associated with early stage type 2 diabetes using in vitro assays. Beverage system with high soluble phenolic phytochemicals potentially provides a higher dose of daily intake of each fruit. The presence of various phenolic bioactives in apple cider and whole blueberry juice, supported with high total soluble phenolic content, antioxidant activity and inhibitory activity α‐amylase, α‐glucosidase and angiotensin‐1‐converting enzyme indicated an improvement of each fruit's functionalities through a synergistic interaction. This research resulted in the optimization of apple cider and blueberry juice combinations and could provide biochemical rationale to further improve the bioactive functionality. This synergistic whole food design may also offer effective, safe and inexpensive strategy for the management of diet‐linked chronic noncommunicable diseases such as early stages of hyperglycemia associated with type 2 diabetes.